2022
DOI: 10.1002/ece3.8615
|View full text |Cite
|
Sign up to set email alerts
|

Snail communities increase submerged macrophyte growth by grazing epiphytic algae and phytoplankton in a mesocosm experiment

Abstract: Submerged macrophytes, phytoplankton, epiphytic algae, and aquatic snails are important taxa in freshwater ecosystems and are widely distributed in various water bodies (Carpenter & Lodge, 1986;Underwood et al., 1992;Zhu et al., 2013). The relationship between producers (e.g., macrophytes, phytoplankton and epiphytic algae) and snails is important in maintaining the function and sta-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 89 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…Elevated temperatures can enhance metabolism and growth, accelerating reproduction and population growth. Nutrient loading, representing increased nutrient levels, fosters the growth of algae and plants, which constitute Radix swinhoei's primary food source [125]. In nutrient-rich waters, they can access more food resources, facilitating their growth and reproduction [126].…”
Section: The Sensitivity Of Different Zoobenthic Species To Various T...mentioning
confidence: 99%
“…Elevated temperatures can enhance metabolism and growth, accelerating reproduction and population growth. Nutrient loading, representing increased nutrient levels, fosters the growth of algae and plants, which constitute Radix swinhoei's primary food source [125]. In nutrient-rich waters, they can access more food resources, facilitating their growth and reproduction [126].…”
Section: The Sensitivity Of Different Zoobenthic Species To Various T...mentioning
confidence: 99%
“…Accordingly, the distribution of macrophytes in the littoral zone is critical for both gastropods and ecosystem functioning, and the role of gastropods is multifaceted. Submerged macrophytes with complex architecture provide a greater surface area for epiphyton, which leads to greater food source [35][36][37][38] and habitat availability, in addition to increased protection from visual predators and diversification of suitable sites for oviposition [39]. Conversely, several studies have confirmed that gastropods can promote macrophyte growth by grazing light-limiting vegetation, which indirectly leads to changes in nutrient regeneration [26,40,41].…”
Section: Introductionmentioning
confidence: 99%
“… 31 These freshwater snails regulate the growth of periphyton, and macrophytes and shells act as the site for algal and periphyton growth. 32 The ability of these snail species to degrade the papers of three types, namely, cardboard (CB), newspaper (NP) , and plain paper (PP), was assessed along with the amount of the cellulose present in the degraded papers and fecal pellet of the snails fed with several types of paper were also estimated. In general, the degradation of paper waste includes mechanical and physical processes 16 18 or microbial activity.…”
Section: Introductionmentioning
confidence: 99%
“…acuta is an indigenous species of North America but invaded globally in freshwater ecosystems . These freshwater snails regulate the growth of periphyton, and macrophytes and shells act as the site for algal and periphyton growth . The ability of these snail species to degrade the papers of three types, namely, cardboard (CB), newspaper (NP) , and plain paper (PP), was assessed along with the amount of the cellulose present in the degraded papers and fecal pellet of the snails fed with several types of paper were also estimated.…”
Section: Introductionmentioning
confidence: 99%